Natural gas liquid (NGL) distillation process using driving force and thermal pinch analysis methods: Energy and economic assessment / Munawar Zaman Shahruddin ... [et al.] - Shahruddin, Munawar Zaman; Asri, Mohamad Hamidi; Mohd Zin, Rohani; Rahimi, Ahmad Nafais; Zubir, Muhammad Afiq; Zahran, Muhammad Fakhrul Islam; Ibrahim, Norazana; Abd Hamid, Mohd Kamaruddin (Universiti Teknologi MARA Shah Alam, 2020)
Distillation column is one of the effective unit operations that is commonly used to separate chemical mixtures. The only drawback of this separation process is its huge energy consumption especially for a multicomponent separation process which involves a series of distillation columns. Therefore, an optimal sequence must be determined to address the issue. This research proposes the methodology to determine the optimal sequence of distillation columns by using driving force method. Then, thermal pinch analysis is applied to obtain further energy saving in the process. The case study selected is a distillation process to recover 5-component of natural gas liquid (NGL) mixture. Based on the input data, the driving force sequence is determined first and simulated together with a conventional sequence (direct sequence). Then, the extracted data from the simulation will be used for thermal pinch analysis via problem table algorithm (PTA). From the results of PTA, energy consumption between both sequences were compared including the energy consumption before and after the Distillation column is one of the effective unit operations that is commonly used to separate chemical mixtures. The only drawback of this separation process is its huge energy consumption especially for a multicomponent separation process which involves a series of distillation columns. Therefore, an optimal sequence must be determined to address the issue. This research proposes the methodology to determine the optimal sequence of distillation columns by using driving force method. Then, thermal pinch analysis is applied to obtain further energy saving in the process. The case study selected is a distillation process to recover 5-component of natural gas liquid (NGL) mixture. Based on the input data, the driving force sequence is determined first and simulated together with a conventional sequence (direct sequence). Then, the extracted data from the simulation will be used for thermal pinch analysis via problem table algorithm (PTA). From the results of PTA, energy consumption between both sequences were compared including the energy consumption before and after the thermal pinch analysis. In addition, economic analysis has been performed as well to indicate which sequence has lower capital and operating costs based on the proposed heat exchanger network (HEN). According to the results, the combination of the driving force and thermal pinch analysis methods has successfully recorded 48% of energy savings and operating cost, and 58.2% capital cost saving compared to the conventional sequence (direct sequence). Therefore, it can be said that the proposed framework has a great potential to be employed towards the process and economic feasible distillation process.